HER2 Splice Site Mutation c.1899-1G>A as the Potential Acquired Resistance to Trastuzumab in a Patient with HER2-Positive Gastric Adenocarcinoma. (20th May 2021) - Jiao, Xiao-Dong; Liu, Ke; Wu, Ying; Zhou, Xin-Cheng; Qin, Bao-Dong; Ling, Yan; Liu, Jun; He, Xi; Du, Haiwei; Xiang, Jianxing; Zang, Yuan-Sheng
Abstract : : The addition of trastuzumab to chemotherapy regimen is the standard of care for human epidermal growth factor receptor 2 (HER2)-positive advanced gastric cancer; however, most patients eventually acquire trastuzumab resistance. Although some resistance mechanisms to trastuzumab-based regimens have been proposed, further understanding is required for developing therapeutic strategies to overcome the resistance. In the present work, we attempted to determine the possible resistance mechanism to trastuzumab in a patient with HER2-positive stage IV gastric adenocarcinoma. In this study, we first report the nucleotide change c.1899-1G>A at the intron 15 acceptor splice site promoting exon 16 deletion of HER2 as the potential mechanism of trastuzumab resistance in HER2-positive gastric adenocarcinoma. Key Points: The combination of trastuzumab with chemotherapy is considered to be the standard therapy for HER2-positive advanced gastric cancer (GC), but most of the patients eventually acquire trastuzumab resistance. The mechanisms of resistance to trastuzumab in GC are poorly characterized. To the best of the authors' knowledge, this study is the first to implicate HER2 c.1899-1G>A, which results in exon 16 skpping, as the acquired resistance mechanism to trastuzumab in HER2-positive gastric adenocarcinoma. This work provides insights into the potential molecular mechanism of trastuzumab resistance, which is crucial in developing effective therapeutic strategies for HER2-positive GC patients refractory to trastuzumab. Abstract : This work attempted to determine the possible resistance mechanism to trastuzumab in a patient with HER2-positive stage IV gastric adenocarcinoma.